Research policy [ejournal]. - ScienceDirect; ScienceDirect Complete Freedom Collection; ScienceDirect Subject Collections - Business, Management and Accounting; ScienceDirect Subject Collections - Decision Sciences; ScienceDirect Subject Collections - Economics, Econometrics, and Finance (Amsterdam Elsevier Science Publishers B.V. (North-Holland), 1971-)
Peer reviewed multidisciplinary journal devoted to the exploration of the policy problems posed by R&D activities and their interaction with economic, social and political processes.
Keywords: Research -- Periodicals; Research -- Management -- Periodicals; Research, Industrial -- Periodicals; Innovation Management